2003
DOI: 10.1096/fj.03-0578fje
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Toll‐like receptor‐2 expression by the Gal‐lectin ofEntamoeba histolytica

Abstract: The Gal/GalNAc lectin (Gal-lectin) of Entamoeba histolytica is a surface molecule involved in parasite adherence to host cells and is the most promising subunit vaccine candidate against amoebiasis. As macrophages are the major effector cells in host defense against amoebas, we studied the molecular mechanisms by which Gal-lectin activates macrophage. Microarray analysis showed that Gal-lectin up-regulated mRNAs of several cytokines and receptor genes involved in proinflammatory responses. The mechanism whereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 47 publications
2
45
0
1
Order By: Relevance
“…Very recently, it has also been demonstrated that Gal/GalNAc lectin of E. histolytica was bound and captured by different target cells and that host cells containing the lectin showed signs of cell damage (56). Furthermore, amebic galectin purified from E. histolytica has been shown to stimulate macrophages to induce TNF-␣ production (57) and TLR-2 expression (58). Therefore, for a better understanding of the signaling role of amebic galectin in cell function it will be extremely important to investigate whether the purified or recombinant forms of amebic galectin induce the ROS-mediated signaling events required for neutrophil apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, it has also been demonstrated that Gal/GalNAc lectin of E. histolytica was bound and captured by different target cells and that host cells containing the lectin showed signs of cell damage (56). Furthermore, amebic galectin purified from E. histolytica has been shown to stimulate macrophages to induce TNF-␣ production (57) and TLR-2 expression (58). Therefore, for a better understanding of the signaling role of amebic galectin in cell function it will be extremely important to investigate whether the purified or recombinant forms of amebic galectin induce the ROS-mediated signaling events required for neutrophil apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Different surface components of trophozoites were shown to be recognized by macrophages via TLR-2 and TLR-4 signaling (31). Upregulated TLR-2 expression was observed in macrophages exposed to Gal/GalNac lectin of E. histolytica, resulting in NF-κB activation and proinflammatory cytokine production (32). Macrophages lacking TLR-2 and TLR-4 showed impaired response to E. histolytica lipopeptidophosphoglycan (LPPG), suggesting an essential role of pattern recognition for the macrophage response (31).…”
Section: Innate Cell-mediated Immunity To E Histolyticamentioning
confidence: 99%
“…Although TLRs are able to recognize a broad spectrum of structurally diverse ligands ranging from small molecules and polynucleotides to lipopeptides from synthetic, host and pathogen sources, there is surprisingly little literature on the direct interaction of TLRs with lectins [6,7]. For example, TLR4 has been shown to respond to a growing catalogue of structurally diverse ligands ranging from the seminal ligand, LPS to taxol [8] and hyaluronan [9].…”
Section: Introductionmentioning
confidence: 99%